Postoperative Morbidity and Mortality of Perforated Peptic Ulcer: Retrospective Cohort Study of Risk Factors among Black Africans in Côte d’Ivoire - Soro Kountele Gona; Mahassadi Kouamé Alassan; Koffi Gnangoran Marcellin; Kissi Ya Henriette; Coulibaly Adama; Assohoun Toussaint; Ehua Adjoba Manuela; Seu Gagon Sylvain; Afum-Adjei Awuah Anthony; Ehua Somian Francis (Gastroenterology Research and Practice)
Introduction. Surgical treatment of perforated peptic ulcer (PPU) is a challenge for surgeons in Africa. Aim. To determine risk factors of postoperative complications or mortality among black Ivoirian patients with PPU. Methods. All 161 patients (median age = 34 years, 90.7 male) operated on for PPU in the visceral and general surgery unit were enrolled in a retrospective cohort study. Variables were studied with Kaplan Meier and Cox proportional hazard models. Results. Among 161 patients operated on for PPU, 36 (27.5%) experienced complications and 31 (19.3%) died. Follow-up results were the incidence of complications and mortality of 6.4 (95% CI: 4.9–8.0) per 100 person-days and 3.0 (95% CI: 1.9–4.0) per 100 person-days for incidence of mortality. In multivariate analysis, risk factors of postoperative complications or mortality were comorbidities (HR = 2.1, P=0.03), tachycardia (pulse rate > 100/minutes) (HR = 2.4, P=0.02), purulent intra-abdominal fluid collection (HR = 2.1, P=0.04), hyponatremia (median value ≤ 134 mEq/L) (HR = 2.3, P=0.01), delayed time of hospital admission > 72 hours (HR = 2.6, P<0.0001), and delayed time of surgical intervention between 24 and 48 hours (HR = 3.8, P<0.0001). Conclusion. The delayed hospital admission or surgical intervention and hyponatremia may be considered as additional risk of postoperative complications or mortality in Black African patients with PPU.